IT Workforce Outsourcing Benefits, Challenges and Success Factors - Systematic Mapping Study - Simões, Carlos Alberto; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Organizations are highly dependent on a competent IT workforce. IT workforce outsourcing has become a strategic choice of organizations where IT structures are increasingly needed to make management processes more efficient, cost-effective, innovative, and flexible. Problem: The adoption of IT workforce outsourcing presents benefits, challenges, and success factors that require proper management. Despite their direct or indirect impact on IT workforce management, workforce performance, and the quality of products and services, many organizations may not be fully aware of these factors. Solution: We identified the benefits, challenges, and success factors associated with IT workforce outsourcing in the academic literature. IS Theory: We based the study on the General Systems Theory as our findings highlight intertwined relations between organizations, processes, and people involved in IT workforce outsourcing. Method: We executed a systematic mapping study using Engineering Village and Scopus digital databases and complemented the results with backward and forward snowballing. Summary of Results: Based on 32 studies, we identified 13 benefits, 24 challenges, and 18 success factors. These encompass issues related to aspects such as outsourcing strategy, service capacity, human resources, contractual aspects, and outsourcing planning. Contributions and Impact in the IS Area: We compared the results with a prior field study involving industry practitioners engaged in IT workforce outsourcing. We highlight the importance of hearing from both practitioners and the academic literature. Based on the results, academia can propose related research while practitioners can propose actions to improve the adoption of outsourcing practices, risk reduction, and the relationship between contractors and suppliers, among others.